PENGUATAN TATA KELOLA KEUANGAN PT PNM MELALUI PROGRAM PENGABDIAN KEPADA MASYARAKAT BERBASIS PENDAMPINGAN - Harry Z Soeratin (Adiba Aisha Amira, 2026)
Strengthening financial governance is an important prerequisite for the sustainability of microfinance institutions, especially those that carry out social mandates and business sustainability simultaneously. This community service activity aims to strengthen financial governance at PT Permodalan Nasional Madani through a participatory and sustainable mentoring programme. The main problems faced by partners include gaps in financial human resource capacity, the complexity of reporting and internal control systems, and limited sustainable technical assistance. The method used in this activity is a practice-based mentoring approach (learning by doing), which includes identifying needs, providing assistance in preparing and organising financial reports, strengthening internal controls, and monitoring and evaluation. The results of the activities show an increase in the capacity of financial human resources in understanding and applying the principles of accountability and transparency, improvements in the reporting system through the structuring of SOPs and increased data reconciliation discipline, and the strengthening of internal controls that are more integrated into daily work processes. The strengthening of financial governance has resulted in more reliable financial information, improved managerial decision-making, and support for the sustainability of microfinance services. This activity confirms that community service-based mentoring is effective in promoting changes in financial governance practices and strengthening the role of universities as strategic partners in institutional capacity building.